2015
DOI: 10.1021/ed500574s
|View full text |Cite
|
Sign up to set email alerts
|

International Organic Chemistry Competition: A Thrilling, Unique Experience

Abstract: The introduction of clickers into the learning environment evolved significantly reflecting major developments in student academic performance. From simple in-class, multiple-choice questions to global international competitions, this innovative tool has managed to combine both education and entertainment into an intuitive and positively reinforcing learning experience. In 2011, the PI was appointed by the International Union of Pure and Applied Chemistry (IUPAC) to represent and coordinate the activities in L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The authors had experiences trying several replacement strategies and found the following options that faculty might explore if e-learning persists as the default mode of teaching from the Fall of 2020. First, we substituted large-class review sessions by prerecording video presentations using video recording software and uploaded on LumiNUS. For synchronous learning, we tried live streaming via online platforms such as YouTube and Facebook. For small-group discussions, we used the breakout rooms on Zoom. This is especially important for flipped courses such as CM1121 .…”
Section: Substitutes For F2f Teaching Practicementioning
confidence: 99%
“…The authors had experiences trying several replacement strategies and found the following options that faculty might explore if e-learning persists as the default mode of teaching from the Fall of 2020. First, we substituted large-class review sessions by prerecording video presentations using video recording software and uploaded on LumiNUS. For synchronous learning, we tried live streaming via online platforms such as YouTube and Facebook. For small-group discussions, we used the breakout rooms on Zoom. This is especially important for flipped courses such as CM1121 .…”
Section: Substitutes For F2f Teaching Practicementioning
confidence: 99%
“…The OC ( Figure 1) has now become a platform of higher education, where students from all over the globe can showcase their skills by solving challenging organic chemistry problems in a dynamic and enthusiastic manner. Following its significant success, a manuscript highlighting the inception, rules, and triumph of the competition was published [12]. Furthermore, in inspiration of the OC and in coordination with the AUB Regional External Programs, the "Across Borders Organic Competition" was organized by the PI at the Afhad University for Women in Sudan (Figure 1).…”
Section: Figure 1 Top Left: Group Photo During the Fourth Internatiomentioning
confidence: 99%
“…Incorporating competitions into chemistry education is another well-studied method for increasing both classroom engagement and morale. Furthermore, competitions are successful in the context of organic chemistry theory and nomenclature. Given the advantages of classroom competitions and the recent development of chemistry-themed serious educational games, ,,, implementing a class competition that teaches organic chemistry skills is a promising avenue toward improving the wellness and chemistry knowledge of social-distancing, distance-learning, organic chemistry students.…”
Section: Introductionmentioning
confidence: 99%